1995
DOI: 10.1128/aem.61.7.2713-2719.1995
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-dependent membrane fatty acid and cell physiology changes in coccoid forms of Campylobacter jejuni

Abstract: The effect of temperature and the availability of nutrients on the transition of spiral Campylobacter jejuni cells to coccoid forms was investigated. Ageing of spiral C. jejuni cells in either nutrient-poor or nutrient-rich environments resulted in the formation of nonculturable coccoid cells at 4, 12, and 25؇C after different periods, with the cells incubated at 4؇C in nutrient-deficient media remaining culturable the longest. To study the phenomenon, ATP levels, protein profiles, and fatty acid compositions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(79 citation statements)
references
References 33 publications
10
69
0
Order By: Relevance
“…The morphological conversion rates of H. pylori into the coccoid form under different types of stress has been investigated by Kusters et al [33], who conclude that this form of H. pylori is a degenerative morphological phase associated with dead bacteria and that the morphological conversion is not an active process. Similar results were reached in a study of Campylobacter jejuni cells during transformation from rod shape into coccoid forms [34]. If the coccoid forms were viable yet smaller in size and volume, the density should theoretically be the same or even higher when compared to the rod-shaped form of H. pylori.…”
Section: Discussionsupporting
confidence: 79%
“…The morphological conversion rates of H. pylori into the coccoid form under different types of stress has been investigated by Kusters et al [33], who conclude that this form of H. pylori is a degenerative morphological phase associated with dead bacteria and that the morphological conversion is not an active process. Similar results were reached in a study of Campylobacter jejuni cells during transformation from rod shape into coccoid forms [34]. If the coccoid forms were viable yet smaller in size and volume, the density should theoretically be the same or even higher when compared to the rod-shaped form of H. pylori.…”
Section: Discussionsupporting
confidence: 79%
“…When CjRV1 cells were inoculated into PBS, CFU counts declined relentlessly at maintenance temperatures of 37, 25 and 10³C reaching the minimum limit of detection (6.25 CFU ml 3I ) within 1^35 days (data not shown). In common with previous reports [1,5], the rate of decline was faster at higher temperatures and accelerated slightly by incubation in aerobic as opposed to microaerobic conditions (data not shown). Exposure of strain 81116 to the same set of maintenance conditions revealed the same overall trends but marginally slower decline rates than CjRV1 (data not shown).…”
Section: Resultssupporting
confidence: 92%
“…These reports have provoked concern that nonculturable cells might constitute a source of human infection which could not be detected by conventional culture. Although production of operationally nonculturable cells which retain biochemical activity has been clearly documented [1,4,5], the proposed capacity for such cells to become readily culturable has been controversial. In particular, attempts at recovery via animal infection studies have yielded con£icting results [2,6^8] and the possibility that regrowth of a small population of culturable cells had been responsible, rather than a change in the growth properties of temporarily nonculturable cells, has been debated [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…cells from chicks injected with nonculturable forms 7 days previously and suggested that it is a degenerative form. Hazeleger et al (1995) did not detect Campylobacter spp. specific antibodies when coccoid cells were given to mice, rabbits and humans, Beumer et al (1992) could not isolate the bacteria from stool samples in a 30-day period after administration of VBNC cells and these cells did not colonize the caecum of day-of-hatch chicks (Ziprin et al 2003) or revert to colonize the caecum in the presence of a normal microflora (Ziprin and Harvey 2004).…”
Section: Viable But Nonculturable Statementioning
confidence: 87%